AGRIBISNIS NENAS DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Lili Budianingsih; Syaiful Hadi; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study was aimed at knowing agribusiness system of pineapple and determine farm income pineapple in Tambang Sub-district by using survey method.Purposive sampling method was used to get 52 pineapple farmers as sample. The result showed total cost per year was Rp.37.719.046,40-/Ha. Production of pineapple was about 34.314 Pcs/Ha/year, and profit was about Rp.56.092.199,16/year. It indicated that the pineapple farming was efficient and value of Retrun Cost Ratio (RCR) was>1 (2,49) indicated  that pineapple farming suitable to be continued too. Post harvest of pineapple farming consist of collecting, sorting, and and transportation, but saving was not done  by farmers. Marketing channel of pineapple farming consist of 4 channels and subsystem institutional was UED-SP, Counseling institution, and government institution. Supporting institution was not good at all yet.  Keywords: Agribusiness, Pineapple